Self-sustaining alkaline seawater electrolysis via forward osmosis membranes - Ke Shi; Hongyi Wan; Keyu Wang; Fumohan Fang; Shiyi Li; Yixing Wang; Linfeng Lei; Linzhou Zhuang; Zhi Xu (Green Energy & Environment)
Seawater electrolysis for hydrogen production faces inherent challenges, including side reactions, corrosion, and scaling, stemming from the intricate composition of seawater. In response, researchers have turned to continuous water splitting using forward osmosis (FO)-driven seawater desalination. However, the necessity of a neutral electrolyte hampers this strategy due to the limited current density and scarcity of precious metals. Herein, this study applies alkali-durable FO membranes to enable self-sustaining seawater splitting, which can selectively withdraw water molecules, from seawater, via concentration gradient. The membranes demonstrates outstanding perm-selectivity of water/ions (∼5830 mol mol−1) during month-long alkaline resistance tests, preventing electrolyte leaching (>97% OH− retention) while maintaining ∼95% water balance (VFO = Velectrolysis) via preserved concentration gradient for consistent forward-osmosis influx of water molecules. With the consistent electrolyte environment protected by the polyamide FO membranes, the NiFe-Ar-P catalyst exhibits promising performance: a sustain current density of 360 mA cm−2 maintained at the cell voltage of 2.10 V and 2.15 V for 360 h in the offshore seawater, preventing Cl/Br corrosion (98% rejection) and Mg/Ca passivation (99.6% rejection). This research marks a significant advancement towards efficient and durable seawater-based hydrogen production.